Answer:
using the formula x/a + y/b =1
a: slope intercept on the x axis
b:slope intersect on the y axis
x/0 + y/3 = 1 (since x/0 is undefined ,the slope doesn't exist and it is impossible for a slope to be linear)
The first four terms of an arithmetic sequence are shown below.
1, 5, 9, 13,......
(a) Write down the nth term of the sequence (general formula).
(b) Calculate the 100th term of the sequence.
(c) Find the sum of the first 100 terms of the sequence.
Answer:
a) n = 4(n-1)+1
b) 397
c) 19900
Step-by-step explanation:
The time required to drive a fixed distance varies inversely as the speed. It takes 40 hr at a speed of 10 km/h to drive a fixed distance. How long will it take to drive the same distance at a speed of 8 km/h?
Answer:
50 hours
Step-by-step explanation:
Given data
Time=40hr
Speed=10km/hr
Let us find the fixed distance first
Speed= distance/Time
10= distance/40
distance= 10*40
distance= 400miles
Now our speed= 8km/h
hence the time is
8= 400/time
time= 400/8
time=50 hours
Hence the time is 50 hours
Solve for the surface area
Answer:
210.7
Step-by-step explanation:
7x8 (and multiply that by 3 for the 3 sides)
7x6.1 (times 2 for the 2 sides and divided by 2 because it is a triangle)
What are the slope and the y-intercept of the linear function that is represented by the equation y - 9x-27?
Answer:
the slope and the y-intercept of the linear function that is represented by the equation y = 9 x minus 27? The slope is –2, and the y-intercept is 9.
Step-by-step explanation:
hope this helps
Find the sum of (x + 5), (–4x –2), and (2x – 1).
PLEASE HELP!!!
Answer:
-x-2
Step-by-step explanation:
x+5 + -4x -2 + 2x -1 = -x -2
Answer:
-x + 2
Step-by-step explanation:
(x + 5), (-4x -2), and (2x -1)
x + (-4x) + 2x) + (5 + -2 + -1)
= -x + 2
PLS HELPPPPPP!!!!!!!!!!
Answer:
x = 30
ABC = 90
ACB = 30
Step-by-step explanation:
We know that if we add the 3 angles of a triangle together, it will come out to be 180 degrees, so..
60 + x + 3x = 180 subtract 60 from both sides and simplify
4x = 120 divide both sides by 4
x = 30
ABC = 3x
ABC = 3(30)
ABC = 90
Regular hexagon ABCDEF is inscribed in circle X and has an apothem that is 6√3 inches long. Use the length of the apothem to calculate the exact length of the radius and the perimeter of regular hexagon ABCDEF. In your final answer, include your calculations.
Answer:
Part A
[tex]The \ circumradius, \ R = \dfrac{a}{cos \left(\dfrac{\pi}{n} \right)}[/tex]
Plugging in the given values we get;
[tex]The \ circumradius, \ R = \dfrac{6 \cdot \sqrt{3} }{cos \left(\dfrac{\pi}{6} \right)} = \dfrac{6 \cdot \sqrt{3} }{\left(\dfrac{\sqrt{3} }{2} \right)} = 6 \cdot \sqrt{3} \times \dfrac{2}{\sqrt{3} } = 12[/tex]
R = 12 inches
The radius of the circumscribing circle is 12 inches
Part B
The length of each side of the hexagon, 's', is;
[tex]s = a \times 2 \times tan \left(\dfrac{\pi}{n} \right)[/tex]
Therefore;
[tex]s = 6 \cdot \sqrt{3} \times 2 \times tan \left(\dfrac{\pi}{6} \right) = 6 \cdot \sqrt{3} \times 2 \times \left(\dfrac{1}{\sqrt{3} } \right) = 12[/tex]
s = 12 inches
The perimeter, P = n × s = 6 × 12 = 72 inches
The perimeter of the hexagon is 72 inches
Step-by-step explanation:
The given parameters of the regular hexagon are;
The length of the apothem of the regular hexagon, a = 6·√3 inches
The relationship between the apothem, 'a', and the circumradius, 'R', is given as follows;
[tex]a = R \cdot cos \left(\dfrac{\pi}{n} \right)[/tex]
Where;
n = The number of sides of the regular polygon = 6 for a hexagon
'a = 6·√3 inches', and 'R' are the apothem and the circumradius respectively;
Part A
Therefore, we have;
[tex]The \ circumradius, \ R = \dfrac{a}{cos \left(\dfrac{\pi}{n} \right)}[/tex]
Plugging in the values gives;
[tex]The \ circumradius, \ R = \dfrac{6 \cdot \sqrt{3} }{cos \left(\dfrac{\pi}{6} \right)} = \dfrac{6 \cdot \sqrt{3} }{\left(\dfrac{\sqrt{3} }{2} \right)} = 6 \cdot \sqrt{3} \times \dfrac{2}{\sqrt{3} } = 12[/tex]
The circumradius, R = 12 inches
Part B
The length of each side of the hexagon, 's', is given as follows;
[tex]s = a \times 2 \times tan \left(\dfrac{\pi}{n} \right)[/tex]
Therefore, we get;
[tex]s = 6 \cdot \sqrt{3} \times 2 \times tan \left(\dfrac{\pi}{6} \right) = 6 \cdot \sqrt{3} \times 2 \times \left(\dfrac{1}{\sqrt{3} } \right) = 12[/tex]
The length of each side of the hexagon, s = 12 inches
The perimeter of the hexagon, P = n × s = 6 × 12 = 72 inches
The perimeter of the hexagon = 72 inches
Answer: radius = 12, perimeter = 72
Step-by-step explanation:
We know that in 30-60-90 right triangles, the hypotenuse is exactly twice the length of the short leg and the long leg is the short leg times √3.
so therefore, if the long leg (apothem) is equal to 6√3, the short leg is equal to 6
long leg = 6√3
long leg = short leg √3
short leg = 6
hypotenuse (radius) = 2(short leg)
hypotenuse (radius) = 2(6)
hypotenuse (radius) = 12
The radius of hexagon ABCDEF = 12 inches
Perimeter = r (sides)
Perimeter = r (6)
Perimeter = 12 (6)
Perimeter = 72
The perimeter of hexagon ABCDEF = 72 inches
The given cylindrical container is used to fill the rectangular prism fish tank with water.
What is the least number of fully cylindrical containers needed to completely fill the fish tank?
The number of full cylindrical containers needed to completely fill the fish tank is 30.
What is a cylinder?In geometry, it is defined as the three-dimensional shape having two circular shapes at a distance called the height of the cylinder.
We know the volume of the cylinder is given by:
[tex]\rm V = \pi r^2 h[/tex]
The volume of a cylinder:
[tex]\rm V = \pi (6/2)^2 (8)[/tex]
V = 72π cubic inches
The volume of cube v = 24×24×12 = 6912 cubic inches
A number of full cylindrical containers are needed to completely fill the fish tank:
= 6912/72π
= 30.55 ≈ 30
Thus, the number of full cylindrical containers needed to completely fill the fish tank is 30.
Learn more about the cylinder here:
brainly.com/question/3216899
#SPJ2
There are 14 cans of soup in a pantry, 7 of which contain vegetable beef soup. What is the probability that a randomly selected can will be vegetable beef soup? Write your answer as a fraction or whole number.
Answer:
1/2
Step-by-step explanation:
There is a 7 in 14 chance of randomly selecting a can of vegetable beef soup. In fraction form, that would be a 7/14 chance. Simplifying the fraction would bring us to 1/2, our final answer.
A messenger earns 2640 per year and pays tax at the rate of 10k On a naira how much tax does he pay in the year
Answer:
264 naira
Step-by-step explanation:
Given that:
Amount earned per year = 2460
Rate of interest paid : 10k per naira earned
Tax paid by messenger per year :
100k = 1 naira
10k = (100/10) = 0.1 naira
Hence 0.1 naira is paid as tax on every naira earned
Total amount paid on 2640 Naira :
Amount paid per naira * total amount earned
(0.1 * 2640) = 264 naira
you deposit $1050 into an account that pays 7.25% interest per year. find the amount after six year given the following:
a) compounded semiannually b) compounded monthly
Figure 1 is dilated to get Figure 2.
What is the scale factor?
Answer:
2/3
Step-by-step explanation:
6/9 in simplest form is 2/3. That's the scale factor :)
Profit, P(x), is the difference between revenue, R(x), and cost, C(x), so P(x) = R(x) - C(x). Which expression represents P(x), if R(x) = 2x^4 – 3x^3 + 2x – 1 and C(x) = x^4 – x^2 + 2x + 3?
Answer:
x^4-3x^3+x^2-4
Step-by-step explanation:
Given the following functions
R(x) = 2x^4 – 3x^3 + 2x – 1 and
C(x) = x^4 – x^2 + 2x + 3
We are to find the profit function P(x)
P(x) = R(x) - C(x)
P(x) = 2x^4 – 3x^3 + 2x – 1 - ( x^4 – x^2 + 2x + 3)
P(x) = 2x^4 – 3x^3 + 2x – 1 - x^4 + x^2 - 2x - 3
Collect the like terms
P(x) = 2x^4-x^4-3x^3+x^2+2x-2x-1-3
P(x) = x^4-3x^3+x^2+0-4
P(x) = x^4-3x^3+x^2-4
Hence the required profit function P(x) is x^4-3x^3+x^2-4
Answer:
x^4-3x^3+x^2-4
Step-by-step explanation:
g(n) = -72*(1/6)^n-1 complete the recursive formula
The recursive formula for g(n) is:
g(1) = -72 (base case)
g(n) = [tex]g(n-1) \times (-1/6)[/tex] (for n > 1)
A recursive formula is a formula that defines a sequence or function by expressing each term in terms of one or more previous terms.
It is a way of defining a sequence or function iteratively, where each term or value depends on the previous terms or values.
To find the recursive formula for [tex]g(n) = -72\times (1/6)^{(n-1)} ,[/tex] we need to express the function in terms of its previous term, g(n-1).
Notice that g(n) can be obtained by multiplying g(n-1) by -1/6.
This is because:
[tex]g(n) = -72\times (1/6)^{(n-1)}[/tex]
[tex]g(n-1) = -72\times (1/6)^{(n-2) }[/tex]
So we can write:
[tex]g(n) = g(n-1) \times {(-1/6) }[/tex]
For similar question on recursive formula.
https://brainly.com/question/29224065
#SPJ11
the volume of a sphere is 4851 cubic cm find its diameter
Answer:
The diameter is 21 cm
Step-by-step explanation:
The formula for the volume of a sphere is V = (4/3)πr³, or (in terms of the diameter) V = (4/3)π(d/2)³. This simplifies to
4πd³ πd³
V = ----------- = -----------
3·8 6
Now equate V = (πd³/6) to 4851 cm³. We must first solve this for d³ and then take the cube root of the result:
πd³ = 4851(6) = 29106.
Dividing this result by π yields 9264.7,
and taking the cube root of this is 21. The diameter is 21 cm
I need an answer! NOT A LINK!!! ASAP!
Answer:
im pretty sure its 14
Step-by-step explanation:
i ned help with this asap. im not well with percentages
Answer:
160
Step-by-step explanation:
Add up all the numbers
48 + 67 + 16 + 29 = 160
Answer: D. 160
Step-by-step explanation:
Find P(A') given that P(A) = 0.75
Answer:
I'm not sure what you're asking if P (A) = 0.75 P(A) is equal to 0.75
Preform the indicated operation. Be sure the answer is reduced.
Answer:
D. [tex]\frac{2x+1}{x-8}[/tex]
Step-by-step explanation:
[tex]\frac{x+1}{x-8} - \frac{x}{8-x} = \\\\\frac{x+1 + x}{x-8} = \\\\\frac{x+1}{x-8} +\frac{x}{x-8} =\\\\\frac{x+1+x}{x-8} =\\\\\frac{2x+1}{x-8}[/tex]
Correct choice is D
What is the solution to the inequality? x/2 > 7
Answer: x > 14
m a th way can help with any similar questions like this !!
Help me plz pretty please
2 x + y = 25 3 x − y = 15
Answer: Yeah and ?
Step-by-step explanation:
Answer:
(15,-5)
Step-by-step explanation:
Help me pls
put them from least to greatest
Answer: -7/10, -0.35, 1/5, 0.95
Step-by-step explanation:
-7/10 = -.7
1/5 = 0.2
Answer:
From least to greatest, the correct order is [tex]-\frac{7}{10}[/tex], -0.35, [tex]\frac{1}{5}[/tex], and 0.95.
Step-by-step explanation:
Since all negative numbers are smaller than positive, you immediately know that [tex]-\frac{7}{10}[/tex] and -0.35 are smaller than [tex]\frac{1}{5}[/tex] and 0.95. The greater the absolute value of a negative number is, the smaller that number is. Because [tex]-\frac{7}{10}[/tex] is -0.7, which has a greater absolute value than -0.35, this means [tex]-\frac{7}{10}[/tex] is the smallest number, and -0.35 is the second smallest number. Since [tex]\frac{1}{5}[/tex] is 0.2 which is smaller than 0.95, the correct order from least to greatest would be [tex]-\frac{7}{10}[/tex], -0.35, [tex]\frac{1}{5}[/tex], and 0.95.
Which function g(x) or f(x) has the equation y=x^2-4
Answer:
f x
Step-by-step explanation:
the equqtion's y intercept is -4 , and f (x) has that intercept
Answer:
f(x)
Step-by-step explanation:
The equation says -4 meaning that it moved down 4 spaces on the y-axis.
Please answer correctly !!!! Will mark Brianliest !!!!!!!!!!!!!!
Answer:
For every 7 books Ethan read, Sadie read 3 books.
Step-by-step explanation:
For every 21 books Ethan read, Sadie read 9 books.
Unsimplified Ratio = 21:9
21 and 9 have a common factor of 3.
Because 21 and 9 share a common factor we can simplify the ratio
21 / 3 = 7
9 / 3 = 3
The new ratio is 7 to 3
So for every 7 books Ethan read, Sadie read 3 books.
What number makes the equation true? 35 + = 42
Answer:
7
Step-by-step explanation:
42 - 35 = 7
Find the unit rate 5 cars for 20 people
Answer:
4 people per car
Step-by-step explanation:
To find the unit rate we would have to do
20/5=4
pls help pls help!!!!! ok ty
Answer:
D
Step-by-step explanation:
Indepedent values basically means the x-values
Also sorry for last answer
What is the equation of a circle with center (−3, 0) and radius 20?
Answer:
(x + 3)^2 + y^2 = 20^2
Step-by-step explanation:
If the center is (-3, 0), then the standard equation of a circle, (x - h)^2 + (y - k)^2 = r^2 becomes (x + 3)^2 + (y - 0)^2 = 20^2, or
(x + 3)^2 + y^2 = 20^2
please send help my way please!!
Answer:
14
Step-by-step explanation:
Answer:
area = 153.94
circumfrence = 43.98
Step-by-step explanation:
A=πr2=π·72≈153.93804
C=2πr=2·π·7≈43.9823